Outcome of schizophrenia twenty years after the diagnosis. - Wijesinghe, D.P.D (My University, 2004)
A sample of patients 20 years after initial diagnosis of Schizophrenia was studied to determine the course and outcome. Follow up assessment of traced patients were done using present state examination, Positive and Negative Syndrome Scale, Social Support Network Questionaire, Disability Assessment functioning and life chart schedule. This study confirms that most relapses of schizophrenia occurring during the first five years after the onset of the illness. It also shows that a large number of patients (64 percentage in this sample) were never readmitted during the twenty years. 46.67 percentage of patients had a good prognosis while 22.85 percentage recovered completely after the initial episode. Duration of psychotic symptoms during the first two years, insidious onset and younger age at the time of onset were significantly associated with poor prognosis. All of the patients in this sample had a good family supportive network. Therefore it was impossible to examine it as a predictor of outcome. The rate of the depression was 17.1 percentage which was a lower rate than other international studies.(PeterMason, Lynn Harrison 1996) The rate of alcohol and drug abuse/dependence was also very low. The suicidal rate was 8.57 percent.